GREEN BANKING, EFISIENSI BIAYA OPERASIONAL (BOPO), DAN PROFITABILITAS: BUKTI EMPIRIS PADA PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2020–2024 - Siregar, Dina Khairuna; Oktavia, Rima; Jefri, Ulfi (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
Environmental degradation and the increasing risks of climate change have encouraged the banking sector to integrate sustainability principles through the implementation of green banking. This study aims to analyze the effect of green banking and operational costs to operating income (BOPO) on the profitability of banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Green banking is measured using the Green Banking Disclosure Index (GBDI), while operational cost efficiency is proxied by the BOPO ratio (Operating Expenses to Operating Income), and profitability is proxied by Return on Assets (ROA). This study employs a descriptive quantitative approach. The results indicate that green banking has no significant effect on profitability, whereas the BOPO ratio has a negative and significant effect on profitability. However, jointly, both variables have a significant effect on profitability. These findings imply that banks need to integrate sustainability principles into their business strategies by shifting credit portfolios toward sustainable sectors rather than focusing solely on short-term profits. Furthermore, green banking should be internalized within banking operations through environmentally friendly practices to improve operational cost efficiency. In addition, banks are required to manage the BOPO ratio efficiently, as operational efficiency plays a crucial role in enhancing profitability and maintaining long-term competitiveness.